Kembali ke Alam untuk Meminimalkan Risiko: Alasan Perempuan Muda Memilih Perawatan Kecantikan Tradisional - Arif Budi Darmawan; Alfira Nuarifia Handitasari (Universitas Padjadjaran, 2021)
The emergence of modernization and globalization, followed by technology, information, and communication, leads Javanese millennial women to start using modern beauty treatment. On the other side, there are groups of millennial women who prefer to use traditional treatment. Research on traditional treatments and Jamu (Indonesian herbal medicine) are mostly focus on its function rather than reasons of people using it. This study explores the factors and reasons of millennial women to return to use traditional beauty treatment rather than modern one. This study applied qualitative in particular phenomenology to explain this trend and to understand the meaning from the perspective of users. This research conducted in Yogyakarta Special Region and involved eight millennial women. Using theory of Ulrich Beck on risk society, this study suggests that the trend of back to natural treatment among millennials is a form of a reflexive modernity. There are reasons of young women to do this; 1) previous experience of adverse effect of modern beauty treatment; 2) the price of traditional beauty treatment is more affordable than modern one; 3) the feasibility of getting basic ingredients for traditional beauty treatment; 4) belief about the good effect of traditional beauty treatment rather than modern one.